A label-free protamine-assisted colorimetric sensor for highly sensitive detection of S1 nuclease activity. Issue 7 (25th February 2020) - Wen, Jiahui; Liu, Yongming; Li, Jingwen; Lin, Hao; Zheng, Yiran; Chen, Yan; Fu, Xiuli; Chen, Lingxin
Abstract : A label-free, simple and rapid colorimetric method for the sensitive detection of S1 nuclease activity based on protamine-assisted aggregation of gold nanoparticles. Abstract : A label-free, sensitive, simple and general colorimetric method was reported to monitor S1 nuclease activity based on protamine-assisted aggregation of gold nanoparticles (AuNPs). Here, protamine, a linear polycation, was used as a medium for causing the aggregation of negatively charged AuNPs by electrostatic interactions, resulting in changes in the surface plasmon resonance (SPR) absorption bands as well as the color of AuNPs. Here, the AuNPs were employed as an indicator to detect the level of S1 nuclease in the solution. Substrate DNA could be cleaved into small fragments by the specific S1 nuclease, which effectively prevents the electrostatic interaction between DNA and protamine and thus facilitates the interaction between protamine and AuNPs. The quantitative analysis of S1 nuclease activity can be performed via directly measuring the changes in the absorption spectra of the AuNPs. Using S1 nuclease as a model analyte, the limit of detection was estimated to be 1.0 × 10 −4 U mL −1 . Furthermore, the proposed concept has been successfully applied in S1 nuclease analysis of serum samples, offering an ultrasensitive strategy for the speedy detection of the nuclease activity and providing a new avenue for high-throughput screening of nucleases and drugs with potential inhibition properties.